2021
DOI: 10.1038/s41467-021-27097-8
|View full text |Cite
|
Sign up to set email alerts
|

ACE2-like carboxypeptidase B38-CAP protects from SARS-CoV-2-induced lung injury

Abstract: Angiotensin-converting enzyme 2 (ACE2) is a receptor for cell entry of SARS-CoV-2, and recombinant soluble ACE2 protein inhibits SARS-CoV-2 infection as a decoy. ACE2 is a carboxypeptidase that degrades angiotensin II, thereby improving the pathologies of cardiovascular disease or acute lung injury. Here we show that B38-CAP, an ACE2-like enzyme, is protective against SARS-CoV-2-induced lung injury. Endogenous ACE2 expression is downregulated in the lungs of SARS-CoV-2-infected hamsters, leading to elevation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 52 publications
(87 reference statements)
1
26
0
Order By: Relevance
“…Recently, the assessment of SARS-CoV-2 reported that S-protein contributes to the downregulation of ACE2 expression on host cells via ubiquitination in COVID-19 cases ( Lei et al, 2021 ). Also, in virus-free analyses, in vivo treatment of virus-free S-protein plus acid-induced injury showed downregulation in mRNA expression and protein of ACE2 receptor ( Yamaguchi et al, 2021 ). Hence, two modes for downregulation of ACE2 in COVID-19 cases have been advised: (i) direct virus attachment-intermediated ACE2 internalization/scaling ( Wang et al, 2008 ) and (ii) lung injury/inflammation-mediated downregulation ( Assiri et al, 2013 ; Imai et al, 2005 ; Yamaguchi et al, 2021 ).…”
Section: Role Of Ace2 In Sars-cov-2 Infectionmentioning
confidence: 99%
“…Recently, the assessment of SARS-CoV-2 reported that S-protein contributes to the downregulation of ACE2 expression on host cells via ubiquitination in COVID-19 cases ( Lei et al, 2021 ). Also, in virus-free analyses, in vivo treatment of virus-free S-protein plus acid-induced injury showed downregulation in mRNA expression and protein of ACE2 receptor ( Yamaguchi et al, 2021 ). Hence, two modes for downregulation of ACE2 in COVID-19 cases have been advised: (i) direct virus attachment-intermediated ACE2 internalization/scaling ( Wang et al, 2008 ) and (ii) lung injury/inflammation-mediated downregulation ( Assiri et al, 2013 ; Imai et al, 2005 ; Yamaguchi et al, 2021 ).…”
Section: Role Of Ace2 In Sars-cov-2 Infectionmentioning
confidence: 99%
“…Post-translational regulation such as intracellular localization in late endosome-mediated viral infection ( Figure 1 ) or post-transcriptional regulation via induction of microRNA expression by NF-kB activation have been reported as molecular mechanisms of pulmonary ACE2 expression ( 21 ). Recently, we have found that SARS-CoV-2 infected hamster lungs also exhibit reduced ACE2 protein expression ( 22 ). Therefore, it is presumed that the expression of ACE2 protein is also decreased in the lung tissue of COVID-19 pneumonia patients, and it is possible that the ACE2 and RAS systems are involved in the pathophysiology of COVID-19.…”
Section: Pulmonary Ace2 Expression and Sars-cov/sars-cov-2 Infectionsmentioning
confidence: 99%
“…In mice treated with Spike protein, decreased expression of ACE2 and increased Ang II levels were observed, and administration of ARB improved severe acute lung injury caused by Spike of the 2013 SARS-CoV ( 20 ). More recently, we administered SARS-CoV-2 Spike protein to a hamster with HCl inhalation-induced ARDS, which showed a similar exacerbation of acute lung injury ( 22 ). Treatment with the ACE2-like enzyme B38-CAP improved severe lung injury ( 22 , 27 ).…”
Section: Role Of Ras/ace2 In the Lung Injury Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations